Елементи церемоніальної колісниці VІІ ст. до нар. Хр. на Тернопільщині - Бандрівський, М. (Інститут українознавства ім. І. Крип'якевича НАН України, 2009)
Materials obtained during the excavations of new burial mound discovered in Middle Dnister region are first presented at the article. It is dated back to VII century B.C. Under ground and stone obstruction, almost rectangular stone square with dimensions 5,2×5,6 meters was found. There are twelve post-pits, surrounded by ditch were situated on the perimeter of this square. Some kind of hiding place was discovered near one of post-pits. It includes six pairs of iron bits with psalias, four bronze fretted zoomorphic heads, four bronze bells, iron knives, handle of bronze mirror, three-blade arrow-head and other artifacts. All these finds are dated, generally, to second half of VII century B.C. and have common features with materials from burials of Middle part of Dnipro River’s basin, Pre-Caucasian region (Krasnoe Znamja burial complex) and also with monuments of Assyria (Nimrod’s palace in Nineveh).